Bee characterization in the sierra central-north region of Veracruz: context and transhumance - Luna Chontal, Giovanni; Roque Peña, Juan Gabriel; Fernández Echeverría, Eduardo; Martínez Mendoza, Eduardo; Díaz Zorrila, Ulises Asrrael; Fernandez Lambert, Gregorio (Revista Mexicana de Ciencias Agrícolas, 2019)
This article presents the result of an investigation carried out from August 2015 to November 2016, to characterize the beekeeping production and transhumant activity of the municipalities of Misantla, Yecuatla, Colipa, Juchique de Ferrer and Tenochtitlan. Interviews are conducted with specialists, experts and honey producers. It is found that the beekeeping activity is carried out for at least 500 families with an average experience of 22 years, with semi-extensive transhumant systems with an average production of 24 kg of honey per beehive, of which 9% have more than 500 beehives working under semi-technified schemes. Among these systems, only 10% of beekeepers have invested in the differentiation of beehive products. The volume of honey generated with production systems of a queen bee per beehive is at least 90 t year-1, with an economic value of 174 000 (US ). It has been found that 90% of beekeepers in the study region transhuman between places in that region and 23% of them do it to another entity. On the other hand, it was also found that access and permission to land are factors that define transhumant routes and identification of suitable areas for apiaries settlement. This research provides a map of areas used as apiaries settlements, as research work, their results deserve the attention of future research to identify spatial zones through systems of geo-positioning, as well as a transhumance program for these locations based on calendars of flowering.